In-situ thermal transport measurement of flowing fluid using modulated photothermal radiometry. (December 2021) - Zeng, Jian; Chung, Ka Man; Adapa, Sarath Reddy; Feng, Tianshi; Chen, Renkun
Highlights: First non-contact in-situ thermal conductivity measurement of flowing fluid. Identify experimental conditions to obtain intrinsic thermal conductivity of fluid. Demonstrate the technique on water, ethanol, and two types of oils. Measure oil from room temperature to 170 °C. Abstract: In situ thermal transport measurement of flowing fluid could be useful for the characterization and diagnosis of practical thermal systems such as fluid heat exchangers and thermal energy storage systems. Despite abundant reports on the ex-situ thermal conductivity measurement of stagnant fluids, a suitable technique for the thermal conductivity measurement of flowing fluid has been rarely reported. This paper presents the thermal conductivity measurement of flowing fluid within a pipe using a non-contact modulated photothermal radiometry (MPR) technique, where the surface of the pipe is heated by an intensity-modulated laser and the heat diffuses into the fluid with suitable modulation frequency. We design a tube section with small wall thickness suitable for the MPR measurements to maximize the sensitivity of the thermal response to the fluid properties while minimizing the lateral heat spreading effect. Intrinsic thermal conductivity of different fluids was obtained within a proper range of frequency and flow velocity where the forced convection effect is negligible. The forced convection effect became prominent at high flowing velocity and at low modulation frequency, leading to higher effective thermal conductivity of the fluid. It is found that the intrinsic thermal conductivity could be obtained when the flow velocity is less than 100 mm/sec and ReD 1/2 Pr 1/3 < 100 for DI water and Xceltherm oil under the specified experimental conditions, where R e D is the Reynolds number and P r is the Prandtl number.